Seismic reservoir characterization and pressure depletion of the Abu Madi Formation in the NW Khilala field, onshore Nile Delta, Egypt - FATTAH, Nadia Abdel; IBRAHIM, Ibrahim Mohamed; ELKAMMAR, Manal (Contributions to Geophysics and Geodesy, 2022)
The Late Messinian Abu Madi Formation represents the most prospective deep reservoir target in the Nile Delta. Hydrocarbon exploration in the Nile Delta over the last few decades has been targeted to understand the Abu Madi reservoir quality and distribution. The integration of rock physics, amplitude versus angle (AVA), seismic interpretation, seismic attributes, and seismic inversion could successfully determine the characteristics of the late Messinian Abu Madi Formation in the North West Khilala (NWKh) field, which is located in the central onshore part of the Nile Delta, Egypt. The NWKh field is located on the eastern margin of the Disouq concession close to producing the West Khilala (WKh) field, with highly heterogeneous reservoir parameters. The reservoir is classified as lacustrine turbidites deposited in semi-isolated Late Messinian Basins. The Abu Madi Formation can be subdivided into upper and lower sand members. It is very common that they are separated by an intraformational shale layer. AVA analysis performed on the top of the Abu Madi reservoir suggested a class 2p. Seismic data were inverted to delineate the overall lateral extent of the reservoir. The prestack inversion process was integrated with rock physics modelling of the wells to generate high-resolution multiple rock property models to characterize the reservoir and observe or investigate different pressure depletion trends. The pressure depletion of the lower Abu Madi in the North West Khilala field was investigated laterally and vertically by the relative/full spectrum inversion and formation modular dynamic tester (MDT) pressure data, respectively. This depletion is due to communication with the West Khilala field, which was produced from the Lower Abu Madi (LAM) sand interval in 2007.